Kutai Inscriptions - Wan Mamat, Wan Ali (Persatuan Sejarah Malaysia, 2013)
The origins and development of the Malay art of writing as in the Malay-Jawi manuscripts were closely related to Islam and the Islamization of the peoples in the Malays Archipelago.Almost all the Malay manuscripts extant were written in the Jawi script, the traditional script of the Malays which were derived from Arabic script. Etymologically, many of the Malay terms relating to the art of writing originated from the Arabic words, for example huruf for letter originated from the Arabic word huruf, kertas for paper originated from the word qartas, dakwat for ink originated from the word dakwat and kalam for pen was from the word qalam. In addition, the great majority of the Jawi manuscripts were translations or adaptions form Arabic books on Islam, biographies and stories of Islamic leaders. This shows the extent of influence of Islamic tradition of writing, especially Arabic, on Malay writing and scholarship.